1993
DOI: 10.1111/j.1600-0765.1993.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of nifedipine in plasma and gingival crevicular fluid in relation to drug‐induced gingival overgrowth

Abstract: The present study investigates the relationship between the pharmacokinetic variables of nifedipine with the incidence and severity of gingival overgrowth in 9 adult male patients medicated with the drug for at least 6 months. Five of the patients had experienced significant gingival changes and were thus designated "responders". The remaining four patients exhibited no gingival overgrowth, and thus acted as a control. A baseline periodontal examination (plaque scores, bleeding index and gingival overgrowth as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…10,15 The results of the present study are in agreement with studies which have reported that the concentration of nifedipine in GCF does not relate to gingival overgrowth degree. 10,15 Similar to the results of this study, Thomason et al 15 could not determine a relationship between GCF and plasma drug concentrations in 63 organ transplant patients. However, in contrast to the present findings, a statistically significant relationship between GCF and plasma nifedipine concentration has been reported.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…10,15 The results of the present study are in agreement with studies which have reported that the concentration of nifedipine in GCF does not relate to gingival overgrowth degree. 10,15 Similar to the results of this study, Thomason et al 15 could not determine a relationship between GCF and plasma drug concentrations in 63 organ transplant patients. However, in contrast to the present findings, a statistically significant relationship between GCF and plasma nifedipine concentration has been reported.…”
Section: Discussionsupporting
confidence: 92%
“…9 It has been shown that several drugs like nifedipine, amlodipine, phenytoin, tetracycline and ciprofloxacin can be detected in GCF. [10][11][12][13][14] The relationship between the pharmacokinetic variables of nifedipine with the incidence and severity of gingival enlargement has been investigated in nine adult males. 10 The results of this study suggested that there was no relationship between plasma/GCF nifedipine concentration and the degree of gingival overgrowth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 It has been reported in one study that nifedipine concentrates in the gingival crevicular fluid up to 90 times the serum concentration and, of the nine patients examined, nifedipine could be found in the crevicular fluid of all five of the patients with gi n gi va l overgrowth and two of the 'non-responders'. 67 While a male predominance has been reported 68 it should be remembered that most studies in this area have not been randomized.The variability of the clinical appearance of this gingival overgrowth is probably related to the level of oral hygiene (Fig. 3b-3d).…”
Section: Gingival Overgrowth Nifedipinementioning
confidence: 99%
“…IL-1α predominates (16) in gingival crevicular fluid and a greater amount of nifedipine is found in gingival crevicular fluid in the patients with periodontal disease (19,20). The aim of this study was thus to investigate the simultaneous effect of nifedipine and IL-1α on cell proliferation and DNA synthesis of gingival fibroblasts from nifedipine responders and non-responders.…”
Section: Introductionmentioning
confidence: 99%